Tracing-at-a-Distance, or a Meaningful Level of Radioactivity - Nicolas Holt (VIEW Journal of European Television History and Culture)
This article argues that radioisotopes – atoms with unstable nuclei which undergo decay and become detectable against less energised backgrounds – can be understood as a form of media, one that challenges the seeing-at-a-distance of the televisual with a ‘tracing-at-a-distance’ of radioactive decay. These energetic entities, largely released in the development and subsequent use of nuclear weapons, became indispensable tools for US ecologists during the Cold War, where tracing radioisotopes became a means to reveal biological pathways and biospheric processes with atomic precision. Thinking radioisotopes within the context of the televisual affords the opportunity to challenge the distinction between inscriptive and transmissional media, while bringing media studies into closer contact with the energy humanities and environmental history.